Mitigation of metal mining influenced water - Gusek, James J.; Figueroa, Linda A. (Management technologies for metal mining influenced water ;, 2009)
Mitigation of Metal Mining Influenced Water is the "how to fix it" volume in a series of six handbooks on technologies for managing metal mine and metallurgical process influenced water. Unlike other texts that focus exclusively on acid drainage from coal mines, this comprehensive series examines both acidic and neutral pH waters from metal mining and metallurgical processes that may impact the environment. The authors take a holistic approach by considering all aspects of the mine life cycle, from planning and design to closure.